Development of a short measure of writing apprehension: Validity evidence and association with writing frequency, process, and performance. (December 2018) - Limpo, Teresa
Abstract: This article reports two studies addressing writing apprehension in undergraduates. Study 1 tested the validity of a reduced version of the 26-item Writing Apprehension Scale (WAS; N  = 194). Exploratory factor analyses revealed a 12-item scale (WAS-12) with two factors (affect and concern), cross-validated in an independent sample ( N  = 220). Further supporting WAS-12 validity and reliability, results revealed good reliability coefficients, along with correlations with external correlates and association with writing performance in the expected direction. Study 2 tested the association of the affect and concern WAS-12 dimensions with writing frequency, process, and performance ( N  = 62). Results showed unique contributions of affect to writing frequency and revising occurrences as well as of concern to planning occurrences, translating occurrences, and writing fluency. Notably, despite there was no association of writing apprehension with writing performance, mediation analysis showed that concern hampered text quality by reducing writing fluency. Practical implications of reported findings are discussed. Highlights: Study 1 validated a 12-item writing apprehension 2-factor scale (affect, concern). Study 2 showed that affect and concern were related to undergraduates' writing. More positive affect was associated with more writing frequency and less revising. More concern was associated with more planning, less translating, and less fluency. High concern hampered writing performance by reducing writing fluency.